Analisis Faktor-Faktor yang Mempengaruhi Niat Pariwisata Pascapandemi Covid-19 di Kota Batam - Verina Verina; Agus Thamrin Reni; Wahyu Satrio Wicaksono; Dela Jane Wijaya; Febrian Wahyu; Ade Gunajulian (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The purpose of this research is to study what drives the people in Batam City to travel/tourism after the recent pandemic, with a focus on the mechanism of citizens perceptions of Covid-19 that influences tourism intentions to travel abroad. The primary data was taken from an internet questionnaire based on Google Form. The number of valid questionnaire data to be processed is 188 questionnaires. The study is a quantitative research with the Structural Equation Model (SEM) as the analytical technique applied. The research model develops a Theory of Planned Behavior (TPB) with several other variables considered relevant to this study. According to the findings, post-pandemic travel plans were significantly influenced by participants attitudes, subjective norms, and perceptions of their own behavioral control. Then perceptions of Covid-19 were also stated to have a significant influence on non-pharmaceutical interventions, while non-pharmaceutical intervention variables could not yet be declared capable of mediating relationship between perceptions of Covid-19 and post-pandemic travel intentions.